Self-assembled polylactic acid (PLA): Synthesis, properties and biomedical applications - Chen, Tianyu; Zhao, Xiaoying; Weng, Yunxuan (Frontiers in Chemistry, 2023)
The surface morphology and topography of cell culture substrates play an important role in cell proliferation and growth. Regulation of the surface microstructure allows the development of tissue culture media suitable for different cells. Polylactic acid (PLA) is a biobased and biodegradable (under defined conditions) polymer with low immunogenicity, nontoxicity, and good mechanical properties, which have facilitated their pharmaceutical and biomedical applications. This review summarizes recent advances in the synthesis and self-assembly of surface microstructure based on PLA materials and discusses their biomedical applications such as cell culturing and tissue engineering.